Integrated assessment of oil pollution using biological monitoring and chemical fingerprinting - Lewis, C.; Guitart, C.; Pook, C.; Scarlett, Alan; Readman, J.; Galloway, T. (Society of Toxicology and Chemistry (SETAC), 2010)
A full assessment of the impact of oil and chemical spills at sea requires the identification of both the polluting chemicals and the biological effects they cause. Here, a combination of chemical fingerprinting of surface oils, tissue residue analysis, and biological effects measures was used to explore the relationship between spilled oil and biological impact following the grounding of the MSC Napoli container ship in Lyme Bay, England in January 2007. Initially, oil contamination remained restricted to a surface slick in the vicinity of the wreck, and there was no chemical evidence to link biological impairment of animals (the common limpet, Patella vulgata) on the shore adjacent to the oil spill. Secondary oil contamination associatedwith salvage activities in July 2007was also assessed. Chemical analyses of aliphatic hydrocarbons and terpanes in shell swabs taken from limpet shells provided an unequivocal match with the fuel oil carried by the ship. Corresponding chemical analysis of limpet tissues revealed increased concentrations of polycyclic aromatic hydrocarbons (PAHs) dominated by phenanthrene and C1 to C3 phenanthrenes with smaller contributions from heavier molecular weight PAHs. Concurrent ecotoxicological tests indicated impairment of cellular viability (p=0.001), reduced immune function (p=0.001), and damage to DNA (Comet assay, p=0.001) in these animals, whereas antioxidant defenses were elevated relative to un-oiled animals. These results illustrate the value of combining biological monitoring with chemical fingerprinting for the rapid identification of spilled oils and their sublethal impacts on biota in situ. Environ. Toxicol. Chem. 2010;29:1358-1366. © 2010 SETAC.